Interferon β, an enhancer of the innate immune response against SARS-CoV-2 infection - Kali, Suresh Kumar (2022)
COVID-19 exhibits a global health threat among the elderly and the population with underlying health conditions. During infection, the host's innate immune response acts as a frontline of defense by releasing cytokines such as type I interferon (IFN α and β) thereby initiating antiviral activity. However, this particular interferon response is interrupted by factors such as SARS-CoV-2 non-structural proteins, aging, diabetes, and germ-line errors eventually making the host more susceptible to illness. Therefore, enhancing the host's innate immune response by administering type I IFN could be an effective treatment against COVID-19. Here, we highlight the importance of innate immune response and the role of IFN β monotherapy against COVID-19.